Efeito do tratamento crônico com derivado da Cannabis Sativa(delta-9- Tetrahidrocanabinol) nos sintomas da menopausa. - TEIXEIRA, Camila Vitória Pinto (2023)
The climacteric is characterized by an altered hormonal state and, frequently, by a decrease in the quality of life, due to the appearance of symptoms that can cause significant discomfort for some women and one of the main symptoms is hot flushes. Therefore, the scientific community has been looking for new medicinal alternatives, such as the use of medicinal plants rich in substances capable of mitigating the effects of the lack of estrogen. Based on this, the present study aims to evaluate the effect of chronic treatment with the derivative of Cannabis sativa, cannabidiol, on menopausal symptoms in an animal model. To carry out the experiment, the animals were divided into 5 groups: Sham operated (SHAM) treated with mineral oil; Ovariectomized patients treated with mineral oil (OVX VEHIC); Ovariectomized patients treated with 1mg/kg of estrogen (OVX E2); Ovariectomized patients treated with 10mg/kg of cannabidiol (OVX CBD); Ovariectomized patients treated with a microdose of estrogen (0.5mg/kg) and cannabidiol (5mg/kg) (OVX CBD E2). During treatment (15 days) the estrous cycle, body weight and body temperature were measured. At the end, the serum, hormonal and histological biochemical parameters of the samples were evaluated. The OVX VEHIC group showed significant changes in body weight, total cholesterol and hormone markers FSH and estrogen. Furthermore, it was the group that presented the greatest uterine atrophy among the ovariectomized patients. An increase in the cutaneous caudal temperature was also observed in relation to the other groups. The OVX E2 group significantly improved these deleterious effects of estrogen depletion compared to the OVX VEHIC group. The OVX CBD group showed an increase in total cholesterol, feed intake and body weight and in the hormone marker estrogen. Uterine atrophy was slightly lower than the vehicle OVX group and in relation to the estrous cycle, it was observed that there was a permanence of 58.3% in the estrus phase. Among the ovariectomized groups, the CBD-treated group had the lowest temperature variation. The OVX CBD E2 group showed significant changes in body weight, feed intake, adipose tissue weight, total cholesterol and estrogen levels. Regarding uterine atrophy, this atrophy was significantly reduced compared to all other groups submitted to ovariectomy and presented cyclicity of 57.14% in the estrus phase. Therefore, it is possible to conclude that the administration of the association of CBD with estrogen presented favorable results in relation to the reversal of some common conditions in menopause, such as the decrease in body weight, reversal of uterine atrophy, decrease in adipose tissue and total cholesterol and also in relation to hot flush induction was statistically significant when compared with the SHAM group. Thus, new studies must be carried out to explore the mechanisms related to these data found in the present study.